Exome Sequencing of 21 Bardet‐Biedl Syndrome (BBS) Genes to Identify Obesity Variants in 6, 851 American Indians. Issue 4 (22nd February 2021) - Day, Samantha E.; Muller, Yunhua L.; Koroglu, Cigdem; Kobes, Sayuko; Wiedrich, Kim; Mahkee, Darin; Kim, Hye In; Van Hout, Cris; Gosalia, Nehal; Ye, Bin; ,; Shuldiner, Alan R.; et al.
Abstract : Objective: In an ongoing effort to identify the genetic variation that contributes to obesity in American Indians, known Bardet–Biedl syndrome (BBS) genes were analyzed for an effect on BMI and leptin signaling. Methods: Potentially deleterious variants (Combined Annotation Dependent Depletion score > 20) in BBS genes were identified in whole‐exome sequence data from 6, 851 American Indians informative for BMI. Common variants (detected in ≥ 10 individuals) were analyzed for association with BMI; rare variants (detected in < 10 individuals) were analyzed for mean BMI of carriers. Functional assessment of variants' effect on signal transducer and activator of transcription 3 (STAT3) activity was performed in vitro . Results: One common variant, rs59252892 (Thr549Ile) in BBS9, was associated with BMI ( P  = 0.0008, β = 25% increase per risk allele). Among rare variants for which carriers had severe obesity (mean BMI > 40 kg/m 2 ), four were in BBS9 . In vitro analysis of BBS9 found the Ile allele at Thr549Ile had a 20% increase in STAT3 activity compared with the Thr allele ( P  = 0.01). Western blot analysis showed the Ile allele had a 15% increase in STAT3 phosphorylation ( P  = 0.006). Comparable functional results were observed with Ser545Gly and Val209Leu but not Leu665Phe and Lys810Glu. Conclusions: Potentially functional variants in BBS genes in American Indians are reported. However, functional evidence supporting a causal role for BBS9 in obesity is inconclusive.